Postharvest Conservation of Mature-Green and Ripe 'Paluma' Guava Stored at Two Temperatures - Morgado, C. M. A. [UNESP]; Durigan, J. F. [UNESP]; Durigan, M. F. B. [UNESP]; Lopes, V. G. [UNESP] (Int Soc Horticultural Science, 2012)
This work aimed to establish the importance of maturation and ripeness stages and the use of refrigeration for the conservation of 'Paluma' guavas. Fruit picked at the mature-green and ripe stages were stored at ambient conditions (21 degrees C and 85% RH) and also at 10 degrees C (85% RH). The fruit were evaluated every 2 or 3 days for weight loss, appearance, decay, color, firmness, soluble solids, titratable acidity, ascorbic acid, total polyphenols extractable content and total antioxidant activity. The fruit stored at 21 degrees C had higher weight loss than those stored at 10 degrees C. Mature-green guavas at 21 degrees C remained in good quality for 6 days, but at 10 degrees C, the preservation period increased to 15 days. Ripe fruit were preserved for 4 days at 21 degrees C, which was extended with refrigeration to 6 days. Mature-green fruit at 21 degrees C had decay in 6 days; while at 10 degrees C decay happened in 18 days. The peel color of mature-green fruits, at 21 degrees C, showed increasing values of luminosity, indicating that its color became lighter (change from green to yellow) and at 10 degrees C it showed constant values until the end of storage. Pulp firmness of mature-green fruit declined during storage as a result of ripening. In ripe fruits such reduction occurred more slowly, since they were softer. The color of the pulp became intense red for mature fruits. Soluble solids were lower in ripe fruit at 21 degrees C, while in mature fruits at 10 degrees C, it increased. The titratable acidity increased in fruits stored at 10 degrees C. The fruits kept at 21 degrees C and the mature guavas kept at 10 degrees C showed no changes in ascorbic acid content. The ripe fruit at 10 degrees C maintained their ascorbic acid levels. Mature guavas, stored at 10 degrees C, had the longest shelf life and higher contents of soluble solids and titratable acidity, with no changes in total polyphenols extractable content and total antioxidant activity.
Keywords: Psidium guajava; refrigeration storage; harvest stage